2019
DOI: 10.1590/1806-9282.65.3.361
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of plasma IL-1b and BDNF can predict resistant depression patients

Abstract: SUMMARY BACKGROUND: There is no strong evidence on the link between inflammatory profile and pattern of drug treatment response in depressive patients that could result in Coronary Artery Disease occurrence. OBJECTIVE: This study aimed to compare the subclinical atherosclerosis markers, inflammatory profile, and BDNF production in Resistant Depression (RD) or Bipolar Affective Disorder (BAD) patients under conventional treatment. METHODS: The population evaluated was comprised of 34 RD, 43 BAD, and 41 contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
3
18
0
1
Order By: Relevance
“…Therefore, inflammatory cytokines, such as IL-6, may mediate the occurrence of neuropsychiatric symptoms in patients infected with SARS-CoV-2. Notably, studies have shown that severe depression, generalized anxiety, post-traumatic stress disorder, and other neuropsychiatric diseases are associated with increased expression levels of inflammatory cytokines, including IL-6, IL-8, IL-10, TNF-α, and their receptors, and higher CRP levels [34,37,38]. Our finding also supports the notion that cytokines play an important role in the pathophysiology of neuropsychiatric symptoms.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, inflammatory cytokines, such as IL-6, may mediate the occurrence of neuropsychiatric symptoms in patients infected with SARS-CoV-2. Notably, studies have shown that severe depression, generalized anxiety, post-traumatic stress disorder, and other neuropsychiatric diseases are associated with increased expression levels of inflammatory cytokines, including IL-6, IL-8, IL-10, TNF-α, and their receptors, and higher CRP levels [34,37,38]. Our finding also supports the notion that cytokines play an important role in the pathophysiology of neuropsychiatric symptoms.…”
Section: Discussionsupporting
confidence: 86%
“… 31 Increased levels of IL-1β could help to identify patients with treatment-resistant depression. 34 Our results suggest that this cytokine may also be involved in burnout syndrome. However, although CBD has been reported to have anti-inflammatory effects, 17 , 18 , 19 , 20 the drug did not prevent increases in IL-1β levels among participants in the current study.…”
Section: Discussionmentioning
confidence: 57%
“…RNA‐sequencing validation by qRT‐PCR showed that the upregulated and downregulated genes were consistent between independent experiments (Figure ). These DEGs were mainly involved in inflammation, neurodevelopment, synaptic plasticity, synaptic transmission, neurotropin binding, neurotrophic binding, signal transduction and cellular communication, which are associated with depressive episodes and therapy . These results suggested that the antidepressant activities of LBRD standard decoction might be achieved by targeting multiple targets in the medial prefrontal cortex.…”
Section: Discussionmentioning
confidence: 85%